Community Transmission of COVID-19 in Sri Lanka: The Debate and its Implications on Action Orientation - A Position Paper from the College of Community Physicians of Sri Lanka - Ruwan Ferdinando; P. B. Buddhika Mahesh; Sameera Senanayake; Iresha Jayawickrama; Chithramali Rodrigo (College of Community Physicians of Sri Lanka, 2021)
No abstract available